Effects of creatine supplementation on renal function - Ricardo Sarmento Pinto Correia (2023)
Introduction: Creatine supplementation is frequently used by athletes. However, its effect on renal function is still a controversial topic in scientific literature. The objective of this review is to deepen, based on current scientific evidence, the effects of creatine supplementation on renal function. Material and Methods: To conduct this literature review, a search was conducted on Pubmed using the following combination of terms "creatine supplementation" and "renal function". Of the 27 articles identified in the database, eight articles were considered eligible, of which two are meta-analyses and six are clinical trials. Results: None of the studies included in this review reported changes in glomerular filtration rate. Conclusion: Despite the reviewed literature not reporting changes in renal function, more studies will need to be conducted with larger samples and appropriate methodology.